Targeting COPD with PLGA-Based Nanoparticles: Current Status and Prospects. (11th March 2022) - Saxena, Juhi; Bisen, Monish; Misra, Aditya; Srivastava, Vijay Kumar; Kaushik, Sanket; Siddiqui, Arif Jamal; Mishra, Neetu; Singh, Abhijeet; Jyoti, Anupam
Abstract : Chronic obstructive pulmonary disease (COPD) is pulmonary emphysema characterized by blockage in the airflow resulting in the long-term breathing problem, hence a major cause of mortality worldwide. Excessive generation of free radicals and the development of chronic inflammation are the major two episodes underlying the pathogenesis of COPD. Currently used drugs targeting these episodes including anti-inflammatory, antioxidants, and corticosteroids are unsafe, require high doses, and pose serious side effects. Nanomaterial-conjugated drugs have shown promising therapeutic potential against different respiratory diseases as they are required in small quantities which lower overall treatment costs and can be effectively targeted to diseased tissue microenvironment hence having minimal side effects. Poly lactic-co-glycolic acid (PLGA) nanoparticles (NPs) are safe as their breakdown products are easily metabolized in the body. Drugs loaded on the PLGA NPs have been shown to be promising agents as anticancer, antimicrobial, antioxidants, and anti-inflammatory. Surface modification of PLGA NPs can further improve their mechanical properties, drug loading potential, and pharmacological activities. In the present review, we have presented a brief insight into the pathophysiological mechanism underlying COPD and highlighted the role, potential, and current status of PLGA NPs loaded with drugs in the therapy of COPD.